Pesantren Education in Indonesia: Efforts to Create Child-Friendly Pesantren - Evi Muafiah; Neng Eri Sofiana; Uswatul Khasanah (Universitas Islam Negeri Mataram, 2022)
Pondok pesantren (Islamic boarding school) has improved in many aspects, including the quality in Indonesia. However, since 2020, sexual and physical abuses have occurred in pesantren that attract public attention. This phenomenon indirectly made many parties question the existence of pesantren. Based on the government directives, pesantren was supposed to be a safe and comfortable environment for learners. This paper presents the efforts of four pesantren in Indonesia to become child-friendly places. Findings based on the qualitative study reported in this paper show that child-friendly pesantren program has been initiated and developed by main figures, such as Kyai/nyai (pesantren leader), ustadz/ustadzah (teachers), and students (santri). Each pesantren has almost the same exertions, namely optimizing three main areas; subjects, management, and infrastructure, but the characteristics of the pesantren still impact the detail stages employed. For instance, Salaf pesantren still strive traditionally, while modern and semi-modern pesantren have begun to adapt to technological advances and current needs.